The High-Resolution Nanostructuring of Si wafer Surface with 10 nm Scale Using a Combined Ion bombarding Technique and Chemical Reaction - Jeon, Hwan-Jin; Jeong, Hyeon Su (한국고분자학회, 2016)
We describe a highly efficient technique for nanostructuring silicon (Si) wafer surfaces with high-resolution (<15 nm) and high aspect ratio (20) structures without any deposition processes. Our strategy is based on advanced secondary sputtering lithography (SSL), which combines physical and chemical plasma etching during an ion bombardment process. Compared with general SSL techniques using Ar gas only, the reactive radicals assisted the SSL and promoted the Si etching rate to simultaneously deposit the etched Si materials onto the side surface of a pre-patterned polymer. In addition, various three-dimensional Si nanostructure shapes could be developed simply by controlling the pre-patterned polymer, thereby providing a simple and versatile approach to customizing this technique.